Governing Road Freight in Eastern and Central Canada: Public Sector Perceptions of Goods Movement Decarbonization - Katsanis, Alexi; Assaf, Gabriel (Canadian Planning and Policy / Aménagement et politique au Canada, 2025)
Road freight governance and decarbonization are often addressed separately in both academic research and professional practice, despite road freight being a significant source of carbon emissions in Canada. This article addresses that gap by examining how public-sector staff perceive intergovernmental relationships related to road freight decarbonization. Through semi-structured interviews with planners and engineers in Ontario, Quebec, New Brunswick, and Nova Scotia, we found that decarbonizing road freight is generally a low priority within broader transportation roles although there is strong interest in developing policies and strategies to reduce emissions from road freight.